1986
DOI: 10.1007/bf02555347
|View full text |Cite
|
Sign up to set email alerts
|

Management of anorectal horseshoe abscess and fistula

Abstract: Over a 10-year period 69 patients were treated consecutively for posterior and anterior horseshoe abscesses and fistulas. Fifty-nine patients had posterior and ten had anterior abscesses or fistulas. There were 52 patients with acute abscess. Treatment consisted of incision and drainage, incision and drainage with primary fistulotomy, incision and drainage with primary fistulotomy and counter-drainage, and incision and drainage with insertion of seton. Seventeen patients with chronic fistulas were treated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 3 publications
2
36
0
1
Order By: Relevance
“…Our findings bear the limitations of a retrospective analysis, but are consistent with those of other authors who have reported similar data in the longer past [10,13,14,[18][19][20][21][22]. We have summarized the main findings from different studies on the utility of setons in the treatment of horseshoe fistulas in Table 1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings bear the limitations of a retrospective analysis, but are consistent with those of other authors who have reported similar data in the longer past [10,13,14,[18][19][20][21][22]. We have summarized the main findings from different studies on the utility of setons in the treatment of horseshoe fistulas in Table 1.…”
Section: Discussionsupporting
confidence: 92%
“…The original Hanley procedure which transected a relevant portion of the posterior sphincter complex has the potential of damaging the sphincter function [9], even if the original series did not identify that as a problem [7,8]. The later modification related to the use of a cutting seton (''modified Hanley procedure'') [10,13,19] to achieve the same goal over a longer period of time (staged slow-motion fistulotomy/ sphincterotomy), hence, allowing the inflammation and scar formation to preserve the anal and sphincter configuration.…”
Section: Discussionmentioning
confidence: 99%
“…LIFT takes note of the old observation that secondary fistula tracks will heal if they are disconnected from the principal fistula which itself is setonized, excised or repaired. Such an observation changed the management of extensive horseshoe ischiorectal abscesses in the 1980s from those large festering ischiorectal wounds that one would frequently see as a resident to the incision/counterincision procedures which would rapidly heal in most patients without incident [6]. The minimalist approach offered by VAAFT requires validation in complicated perianal Crohn's disease but it would appear that its potential value makes intuitive sense in the absence of available prospective data.…”
Section: Sirmentioning
confidence: 99%
“…13 ⁄ 21 Cox et al [36] 4 ⁄ 8 Culp [26] 3 ⁄ 20 Decanini-Terán et al [37] 0 ⁄ 42 Deshpande et al [30] 0 ⁄ 397 Durgan et al [38] 2 ⁄ 10 Dziki and Bartos [39] 12 ⁄ 32 † Fasth et al [40] 0 ⁄ 7 Flich Carbonell et al [41] 3 ⁄ 19 García-Aguilar et al [42] 8 ⁄ 12 Gonzalez-Ruiz et al [43] 0 ⁄ 31 Graf et al [44] 11 ⁄ 29 4 ⁄ 4 Gurer ‡ et al [25] 0 ⁄ 17 Hämäläinen and Sainio [45] 22 ⁄ 35 Hamel et al [46] 0 ⁄ 12 Hammond et al [47] 4 ⁄ 16 Hasegawa et al [48] 15 ⁄ 28 Held et al [49] 0 ⁄ 9 Ho et al [20] 3 ⁄ 46 † Isbister and Al Sanea ‡ [50] 17 ⁄ 47 † Joy and Williams [51] 5 ⁄ 10 Malouf et al [52] 1 ⁄ 3 McCourtney and Finlay [53] 3 ⁄ 16 Mentes et al [54] 4 ⁄ 20 Misra and Kapur [55] 0 ⁄ 53 Mohite et al [31] 0 ⁄ 114 Pescatori et al [56] 3 ⁄ 17 Qureshi et al [57] 2 ⁄ 4 Shukla et al [21] 8 ⁄ 155 Tahir § [58] 5 ⁄ 9 Theerapol et al [59] 0 ⁄ 41 Tocchi et al [60] 4 ⁄ 28 Vatansev et al [61] 5 ⁄ 32 Walfisch et al [62] 0 ⁄ 23 Williams et al [63] 8 ⁄ 13 Zbar et al [22] 3 ⁄ 34 Average rates (%) 15.9% 100% 10.5%…”
mentioning
confidence: 99%